Case report: Diagnostic reconceptualization in the DSM-V on somatoform disorders - Ibarra Patrón, Diana; Medina Vidales, Guillermo; Garza Guerrero, C. (UANL. Facultad de Medicina, 2015)
Psychosomatic disorders are among the most common psychiatric disorders in general practice, with a prevalence of 16%. These patients often turn to different general practitioners and/or non-psychiatric specialists for long periods of time and represent a diagnostic and therapeutic challenge, as the possible organic component makes it complex and difficult to manage. The reported case is a 24-year-old male patient with a diagnosis of Somatic Symptoms Disorder and multiple psychiatric comorbidities. The purpose of this study is to review the reconceptualization of Somatoform Disorders’ DSM-5 diagnosis, which can be useful for psychiatrists and non-psychiatric physicians for the approach and management of these patients.